2013
DOI: 10.5826/dpc.0301a07
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of non-pigmented eccrine poromas: study of Mexican cases

Abstract: Background:Eccrine poroma is a benign neoplasm that can mimick a malignant neoplasm dermoscopically. The characteristic vascular pattern of this tumor has not been established.Objective:To evaluate dermoscopic features of non-pigmented eccrine poroma in Mexican patients.Method:We retrospectively studied histologically proven cases of eccrine poroma from three Mexican hospitals analyzed by four dermoscopists.Results:Thirteen cases were studied. A polymorphous vascular pattern was found in most cases. Four prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Lesion morphology (macule, papule, plaque, nodule, tumour), number of colours and maximum diameter (in millimetres) were recorded. A comprehensive list of dermoscopic structures reported to be present in poromas was created (Data , Supporting Information) . After careful appraisal of previous descriptions and consensus amongst the reviewers, cherry‐blossom vessels, flower‐like vessels, floral vessels, chalice‐like vessels and leaf‐like vessels were categorized as structure called branched vessels with rounded endings, defined as branched vessels with looped or coiled terminal endings that characteristically have a rounded silhouette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion morphology (macule, papule, plaque, nodule, tumour), number of colours and maximum diameter (in millimetres) were recorded. A comprehensive list of dermoscopic structures reported to be present in poromas was created (Data , Supporting Information) . After careful appraisal of previous descriptions and consensus amongst the reviewers, cherry‐blossom vessels, flower‐like vessels, floral vessels, chalice‐like vessels and leaf‐like vessels were categorized as structure called branched vessels with rounded endings, defined as branched vessels with looped or coiled terminal endings that characteristically have a rounded silhouette.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive list of dermoscopic structures reported to be present in poromas was created (Data S1, Supporting Information). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] After careful appraisal of previous descriptions and consensus amongst the reviewers, cherry-blossom vessels, flower-like vessels, floral vessels, chalice-like vessels and leaf-like vessels were categorized as structure called branched vessels with rounded endings, defined as branched vessels with looped or coiled terminal endings that characteristically have a rounded silhouette. We considered milky-red areas, pink-white structureless areas, pink homogeneous area and creamy red background as one feature called milky-red areas, defined as structureless areas with pink to white-red areas.…”
Section: Blinded Lesion Evaluationmentioning
confidence: 99%
“…Shalom et al also reported this finding in the largest series regarding the dermoscopy of eccrine poromas [11] . Dominguez Espinosa proposed the term -cherry-blossom‖ and -chalice-form‖ to better describe these structures [6] . In our case, we added a -cactus-like‖ vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a limited number of studies regarding dermoscopy of eccrine poroma to date. As it is predominantly a non-pigmented neoplasm, its dermoscopic evaluation should be focused doi: 10.18282/jsd.v1.i3.55 on the vascular patterns, as these have been described in previous studies [3][4][5][6][9][10][11] . The evaluation of the vascular patterns under dermoscopy requires a proper techniqueperformed with a contact liquid, preferably ultrasound gel, and with slight pressure applied on the lesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation